(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the results of postoperative pain relief after basal cell carcinoma surgery using Fentanyl PCA versus intravenous Paracetamol at the National Hospital of Dermatology and Venereology in 2023. Subjects and methods: This was a cross-sectional descriptive study on 40 patients who underwent surgery for basal cell carcinoma at the National Hospital of Dermatology and Venereology from March to October 2023. The 40 patients were divided into two equal groups: one group received Fentanyl PCA, and the other group received intravenous Paracetamol. Results: Postoperatively, the mean VAS score for both groups was 5.8-5.9 points. For the Fentanyl PCA group, the postoperative VAS scores at 6 hours, 12 hours, 24 hours, and 72 hours were 4.05 ± 0.39; 2.95 ± 0.39; 2.35 ± 0.49; and 1.05 ± 0.22, respectively. For the intravenous Paracetamol group, the postoperative VAS scores at 6 hours, 12 hours, 24 hours, and 72 hours were 5.70 ± 0.57; 4.15 ± 0.49; 3.75 ± 0.55; and 1.90 ± 0.45, respectively. At discharge, both groups were pain-free with a VAS score < 1 point. Adverse effects were higher in the Fentanyl PCA group (25%) than in the intravenous Paracetamol group (15%) with p > 0.05. Conclusion: Fentanyl PCA pain relief compared to intravenous Paracetamol pain relief showed superiority in the first 72 hours after surgery. Pain levels during movement were lower in the Fentanyl PCA group than in the intravenous Paracetamol group (p < 0.05). At the time of discharge, pain levels during movement in the intravenous Paracetamol group had decreased significantly, comparable to the Fentanyl PCA group. Adverse effects in both groups were not statistically different (p > 0.05).